2021
DOI: 10.1111/scs.12986
|View full text |Cite
|
Sign up to set email alerts
|

Sámi language in Norwegian health care: ‘He speaks good enough Norwegian, I don’t see why he needs an interpreter’

Abstract: Introduction The Indigenous people of Norway are legally entitled to use their Sámi language in encounters with healthcare services, yet these encounters are generally conducted in Norwegian language. The right to Sámi language and culture in health is particularly relegated when Sámi healthcare personnel is not present. This neglect of Sámi language and culture in the Norwegian healthcare system impacts on the quality of care Sámi patients receive. Aim This paper describes and interprets healthcare interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(52 reference statements)
0
3
0
1
Order By: Relevance
“…While previous studies have indicated that cultural factors posed barriers for the Sámi to access healthcare [ 43 , 44 ], none of those variables used in this study seemed to have played a role during the pandemic.…”
Section: Discussionmentioning
confidence: 69%
“…While previous studies have indicated that cultural factors posed barriers for the Sámi to access healthcare [ 43 , 44 ], none of those variables used in this study seemed to have played a role during the pandemic.…”
Section: Discussionmentioning
confidence: 69%
“…What essentially distinguishes the regulation on the New National Guideline for Sámi Nursing Education 2021, from the regulation on the Norwegian National Guideline for Nursing Education 2019, is the addition of a new subject area, namely the health and social consequences of the Norwegianization policy (Kunnskapsdepartementet, 2019, 2021). Since this field of knowledge had not previously been taught in nursing education in Norway, nurses were unfamiliar with this aspect of interaction with Sámi patients (Engenes et al, 2022; Mehus et al, 2018, 2019). Both guidelines for nursing education in Norway are in accordance with the European Directive 2005/36/EC on the recognition of professional qualifications with subsequent amendments 2013/55/EU.…”
Section: The New National Guideline For Sámi Nursing Education Passed...mentioning
confidence: 99%
“…Rein okkens instinkter styrer denne tiden. Det kan også vaere at pasienten eller de pårørende opplever en språkbarriere mot å kontakte hjelpeapparatet utenfor sin egen samiskspråklige kommune (12,(14)(15)(16).…”
Section: Det Er Samhandlingsutfordringer Mellom Parteneunclassified